2018
DOI: 10.1080/00222895.2017.1423019
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Vision and Surface Compliance on Balance in Untrained and Strength Athletes

Abstract: The purpose of this investigation was to evaluate the effect of the removal of vision and/or surface compliance on postural stability in strength athletes who habitually use free-weights and compound movements in their training (i.e., powerlifters, Olympic weightlifters), and untrained individuals. Static and dynamic balance testing was performed with eyes open or closed on stable and memory foam surfaces. Both groups had similar increases in postural sway area and velocity during quiet standing testing; where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
3
6
0
Order By: Relevance
“…We also found that balance performance was largely affected by vision and floor condition, and individuals swayed more with eyes closed, and on the unstable floor. These findings also agree well with previous findings, where impaired visual input decreases postural stability and unstable floor affects somatosensory inputs, resulting in poor balance [10,12,[23][24][25][26][27][28][29].…”
Section: Discussionsupporting
confidence: 93%
“…We also found that balance performance was largely affected by vision and floor condition, and individuals swayed more with eyes closed, and on the unstable floor. These findings also agree well with previous findings, where impaired visual input decreases postural stability and unstable floor affects somatosensory inputs, resulting in poor balance [10,12,[23][24][25][26][27][28][29].…”
Section: Discussionsupporting
confidence: 93%
“…Most remarkable was that removing vision on the firm and foam surfaces had a more pronounced effect for the runners compared to the weightlifters, suggesting the weightlifters had a heightened ability to utilize compensatory sensory information stemming from either vestibular or somatosensory sources. This result is consistent with a previous study comparing young adult (18‐30 years) national level competitive Olympic and power weightlifters to a healthy group of untrained individuals 35 . Specifically, during a limits of stability task under EO/EC visual conditions and FI/FO surfaces, Bryanton and Bilodeau 35 reported that the weightlifters were less affected by changing sensory conditions than the untrained participants.…”
Section: Discussionsupporting
confidence: 91%
“…This result is consistent with a previous study comparing young adult (18‐30 years) national level competitive Olympic and power weightlifters to a healthy group of untrained individuals 35 . Specifically, during a limits of stability task under EO/EC visual conditions and FI/FO surfaces, Bryanton and Bilodeau 35 reported that the weightlifters were less affected by changing sensory conditions than the untrained participants. Taken together, these findings suggest Olympic weightlifting may promote a heighted ability to use vestibular and/or somatosensory sources for balance, although the underlying mechanisms for this phenomenon remain to be explored.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations